Advancements in the diagnosis and management of premature ventricular contractions in pediatric patients - Zhu, Wenjing; Yuan, Hui; Lv, Jianli (Frontiers in Pediatrics, 2024)
Background: Premature ventricular contractions (PVCs) are relatively common arrhythmias in the pediatric population, with implications that range from benign to potentially lifethreatening. The management of PVCs in children poses unique challenges, and recent advancements in diagnostic and therapeutic options call for a comprehensive review of current practices.Methods: This review synthesizes the latest literature on pediatric PVCs, focusing on publications from the past decade. We evaluate studies addressing the epidemiology, pathophysiology, diagnosis, and treatment of PVCs in children, including pharmacological, non-pharmacological, and invasive strategies.Results: The review identifies key advancements in the non-invasive detection of PVCs, the growing understanding of their genetic underpinnings, and the evolving landscape of management options. We discuss the clinical decision-making process, considering the variable significance of PVCs in different pediatric patient subgroups, and highlight the importance of individualized care. Current guidelines and consensus statements are examined, and areas of controversy or limited evidence are identified.Conclusions: Our review underscores the need for a nuanced approach to PVCs in children, integrating the latest diagnostic techniques with a tailored therapeutic strategy. We call for further research into long-term outcomes and the development of risk stratification tools to guide treatment. The potential of emerging technologies and the importance of multidisciplinary care are also emphasized to improve prognoses for pediatric patients with PVCs.